2022
DOI: 10.25251/skin.6.6.4
|View full text |Cite
|
Sign up to set email alerts
|

The Integrated 31-Gene Expression Profile Test (i31-GEP) for Cutaneous Melanoma Outperforms the CP-GEP at Identifying Patients who can Forego Sentinel Lymph Node Biopsy when Applying NCCN Guidelines

Abstract: Introduction: Eighty-eight percent of patients who receive a sentinel lymph node biopsy (SLNB) receive a negative result. Current guidelines suggest avoiding SLNB if the risk of positivity is <5%. A low threshold for performing SLNB indicates worry about missing positive nodes but results in many unnecessary biopsies. The integrated 31-gene expression profile (i31-GEP) test combines the 31-GEP with Breslow thickness, age, ulceration, and mitotic rate using a validated neural network algorithm to identify pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…After screening the articles, 32 met inclusion criteria and were distributed to the panelists for review prior to the roundtable discussion. Of these articles, the number of papers that specifically studied the validity, accuracy, or clinical utility of each test was: 22 for the 31-GEP test 4,[19][20][21][22][23][24][26][27][28][29][30][31][34][35][36][37][38][39][40][41][42] , 2 for the 11-GEP test 11,34 , and 7 for the 8-GEP + CP test. 5,13,23,[43][44][45][46]…”
Section: Comprehensive Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…After screening the articles, 32 met inclusion criteria and were distributed to the panelists for review prior to the roundtable discussion. Of these articles, the number of papers that specifically studied the validity, accuracy, or clinical utility of each test was: 22 for the 31-GEP test 4,[19][20][21][22][23][24][26][27][28][29][30][31][34][35][36][37][38][39][40][41][42] , 2 for the 11-GEP test 11,34 , and 7 for the 8-GEP + CP test. 5,13,23,[43][44][45][46]…”
Section: Comprehensive Literature Searchmentioning
confidence: 99%
“…For the 8-GEP + CEP test, a validation study analyzing the test's ability to predict SLNB positivity found that this model has a NPV of 90.5% (95% Confidence Interval [CI]: 77.9-96.2%) in T1-4 CMs. 44 In comparing the three GEP tests, the panel consensus was that there were significantly more studies supporting the validity, accuracy, and clinical utility of the 31-GEP test compared to the 11-GEP and 8-GEP + CP tests (22 studies validating the 31-GEP test 4,[19][20][21][22][23][24][26][27][28][29][30][31][34][35][36][37][38][39][40][41][42] , compared to just 2 studies validating the 11-GEP test 11,34 and 7 studies validating the 8-GEP + CP test 5,13,23,[43][44][45][46] ). Based on the limited studies for the 8-GEP + CP and the 11-GEP test, the panel concluded that there was insufficient data to assess their validity and utility or currently recommend usage in the clinical setting until further studies are performed.…”
Section: Consensus Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation